Pendidikan Agama Islam Inklusif: Pendekatan Literasi Untuk Menjangkau Semua Anak - Damanik, Muhammad Zein; Utami, Nadia Dwi; Ripandi, Abdul Juki; Khotimah, Khusnul (TARBIYAH, 2024)
This study aims to examine the concept, implementation, and challenges of inclusive Islamic religious education (PAI) through a literature study approach. Inclusive education is one of the main principles in the Indonesian education system to ensure the rights of every child, including children with special needs, in obtaining religious education. This research adopts a descriptive-analytical literature study method by reviewing books, scientific journals, and policy documents. The results show that inclusive PAI education still faces challenges in the form of a lack of trained human resources, limited facilities, and an adaptive curriculum. Therefore, this study recommends teacher training, infrastructure provision, and curriculum revision to be more responsive to student diversity.